Adsorption of Chromium(VI) onto Freshwater Snail Shell-Derived Biosorbent from Aqueous Solutions: Equilibrium, Kinetics, and Thermodynamics - Xuan Hoa Vu; Lan Huong Nguyen; Huu Tap Van; Dinh Vinh Nguyen; Thu Huong Nguyen; Quang Trung Nguyen; L. T. Ha (Journal of Chemistry)
In this study, freshwater snail shells (FSSs) containing CaCO3 were used as a low-cost biosorbent for removing Cr(VI) from aqueous solutions. The characteristics of FSS and mechanism of Cr(VI) adsorption onto FSS were investigated. The FSS biosorbent was characterized using nitrogen adsorption/desorption isotherm, X-ray diffraction, scanning electron microscopy with energy dispersive spectroscopy, and Fourier transform infrared spectroscopy. The adsorption mechanism was determined by conducting various batch adsorption experiments along with fitting experimental data with various adsorption models. Batch adsorption experiments were conducted as a function of solution pH, contact time, biosorbent dose, and initial Cr(VI) concentration. Results indicated that pH = 2, a contact time of 120 min, and an initial Cr(VI) concentration of 30 mg/L at 20°C were the best conditions for adsorption of Cr(VI) onto FSS. The Cr(VI) adsorption onto FSS decreased with an increase in temperature from 20 to 40°C. The obtained maximum adsorption capacity was 8.85 mg/g for 2 g/L of FSS dose with 30 mg/L of initial Cr(VI) at 20°C. The adsorption equilibrium data fit well with the Sips and Langmuir isotherm models at 20°C with a high R2 of 0.981 and 0.975, respectively. Also, a good correlation between the experimental data and the pseudo-second-order model was achieved, with the highest R2 of 0.995 at 20°C. The adsorption mechanisms were electrostatic interaction and ion exchange. Simultaneously, this mechanism was also controlled by film diffusion. The Cr(VI) adsorption process was irreversible, spontaneous (−∆G°), exothermic (∆H° is negative), and less random (∆S° is negative). In conclusion, freshwater snail shells have the potential as a renewable adsorbent to remove toxic metals from wastewater.